Dynamic relations among COVID-19-related media exposure and worries during the COVID-19 pandemic. Issue 8 (3rd August 2022) - Schmidt, Andrea; Brose, Annette; Kramer, Andrea C.; Schmiedek, Florian; Witthöft, Michael; Neubauer, Andreas B.
Abstract: Objectives: This study investigated how COVID-19-related media exposure during the COVID-19 crisis was related to same-day and next-day COVID-19-related worries. Design: A 21-day diary study was conducted between late March and late April 2020 in Germany. Main Outcome Measures: Hypotheses were tested in a sample of 561 participants ( M age = 42.79, SD age = 6.12). Every evening, participants indicated their exposure to COVID-19-related media (e.g., TV, print, online) and their COVID-19-related worries. Results: Same-day analyses showed that participants reported more COVID-19-related worries on days with higher exposure to COVID-19-related media. Dynamical structural equation models provided evidence for a reciprocal cycle across days: Higher media exposure at one day predicted higher worries the next day, and higher worries at one day also predicted higher media exposure the next day. Individuals with high trait anxiety reported an enhanced general level of media exposure during the 21 days of assessment, and individuals high in neuroticism and anxiety reported an enhanced level of worries. Conclusion: These findings suggest a self-reinforcing cycle whereby consuming crisis-related media and worrying reciprocally influence each other across days, possibly amplifying adverse effects of the COVID-19 crisis and other crises alike on mental and physical health.